Insulinoterapia e psicoterapia di gruppo: valore psicoterapeutico del “senso della schizofrenicità” - Fagioli, Massimo (Il sogno della farfalla, 2010)
Following on from Massimo Fagioli’s 1962 article on delirous perception, which appeared in the 3rd number, 2009 of this magazine, we are now proposing another writing by the same author, on insulintherapy and group psychotherapy originally published in 1963. The A. describes how the doctor and a social worker who practiced insulintherapy gave rise to a psychotherapic group. The first relationship with the patient, so as to create a contact with the autistic schizophrenic, can come about when the therapists are able to approach the schizophrenic patient through the “sense of schizophrenicity”. After having established an interhuman relation, the interpersonal dynamics are based on a therapeutic couple which permits the patient to live out a new experience with new parents in a concrete way. The author also highlights the fact that the group is based exclusively on interpersonal relations without any prior organization.